REGULATION OF PRE-START STATES OF JUDOISTS AT THE STAGE OF SPORTSMANSHIP IMPROVEMENT - Zebzeev, Vik.V.; Tunev, A.L.; Zdanovich, O.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to theoretically and methodically substantiate the method of regulation of the pre-start states of judo wrestlers at the stage of improving sportsmanship. Methods and structure of the study. A survey was conducted among judoists of the Perm region, who were at the stage of improving their sportsmanship. The practical experience of coaches of the judo club "Bars" (Perm) and the municipal budgetary sports and health club "Judo and Sambo" (Tchaikovsky), as well as psychologists of the regional judo federation, is summarized. Results and conclusions. Based on the results of the analysis of literary sources on the topic of research and generalization of the experience of judo coaches and sports psychologists, an innovative methodology was developed based on the cumulative implementation of the means, methods and conditions for regulating pre-start states and aimed at achieving the state of combat readiness of judokas at the stage of improving sportsmanship.